The effect of perceived quality and value on express delivery services trust during pandemic Covid 19 - Firdaus, Fika Fahmi; Sutarso, Yudi (Universitas Hayam Wuruk Perbanas, 2022)
During the Covid-19 pandemic, public mobility restriction policies were implemented to prevent the new coronavirus spread. In this period, express delivery services have played an essential role in transporting packets between areas supporting everyday life. This study examines the role of perceived quality and value on brand trust in express delivery services, namely J&T Express Indonesia, the top brand courier service in Indonesia. The researchers employed a purposive sampling and involve 162 respondents of the customer. The study collected data through questionnaires and analyzed using the Partial Least Square-Structural Equation Model. The critical finding showed that perceived quality (excitement, enjoyment, bonding with, and reliability) positively affected the perceived value and brand trust. The other result shows that perceived value (good value, acceptable, good deal, competitive, like, feel-good) affected brand trust. The study’s implication suggests the strategy for express delivery services to enhance perceived quality and value for further increasing customer trust.